Black Lives Matter’s Digital Activism Strategy in Transnationalizing the Police Brutality Issue in Europe in 2020 - Kallapagi, Pramitha Sindhu; Hidayatullah, Nur Luthfi (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2023)
This research tends to examine Black Lives Matter’s Digital Activism Strategy in Transnationalizing the Police Brutality Issue in Europe in 2020. The authors tend to describe how social movements against racism and police brutality which originated in the United States could spread to Europe, in a scale which has not happened previously before Black Lives Matter. This research uses descriptive qualitative research method. The results of this research show that Black Lives Matter has used digital activism strategy in Trans-nationalizing the police brutality issue in Europe in 2020 by providing accessibility, visibility, popularity, and ecosystem. In terms of accessibility, Black Lives Matter provides to a digital network capable of distributing information. Besides that, Black Lives Matter increases visibility by showing the uniqueness of Black Lives Matter as compared to other movements. Next, Black Lives Matter could attract many supporters, which increased its popularity. Finally, Black Lives Matter could spread the movement in other regions based on similar roots, routers and routes, proofing its suitability in the European society’s ecosystem